Conditions for the Long‐Term Preservation of a Deep Brine Reservoir in Ceres. Issue 4 (19th February 2019) - Castillo‐Rogez, Julie C.; Hesse, M. A.; Formisano, M.; Sizemore, H.; Bland, M.; Ermakov, A. I.; Fu, R. R.
Abstract: We propose a new internal evolution model for the dwarf planet Ceres matching the constraints on Ceres' present internal state from the Dawn mission observations. We assume an interior differentiated into a volatile‐dominated crust and rocky mantle, and with remnant brines in the mantle, all consistent with inferences from the Dawn geophysical observations. Simulations indicate Ceres should preserve a warm crust until present if the crust is rich in clathrate hydrates. The temperature computed at the base of the crust exceeds 220 K for a broad range of conditions, allowing for the preservation of a small amount of brines at the base of the crust. However, a temperature ≥250 K, for which at least 1 wt.% sodium carbonate gets in solution requires a crustal abundance of clathrate hydrates greater than 55 vol.%, a situation possible for a narrow set of evolutionary scenarios. Plain Language Summary: We search internal evolution models of dwarf planet Ceres that match the observations returned by the Dawn mission. A key feature to be reproduced is the long‐term persistence of liquid below the crust, at about 40 km depth, as suggested by the observed topography. The possibility for the occurrence of liquid in Ceres at present depends on the presence of insulating material in the crust, for example, in the form of gas hydrates. The latter are also suggested from geophysical and geological observations and geochemical modeling. Our modeling shows in these conditions that liquid can be preserved for a wide range of evolutionary scenarios. Key Points: Brines can be preserved in Ceres if the crust is enriched in clathrate hydrates Lateral variations in clathrate content can drive variations in surface heat flux and topography response